2007
DOI: 10.1359/jbmr.070619
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Loop in the Bim–Caspase-3 Axis Regulating Apoptosis and Activity of Osteoclasts

Abstract: Proapoptotic Bcl-2 family member Bim plays an essential role in the osteoclast apoptosis and is degraded through ubiquitin/proteasome pathways in a caspase-3-dependent manner. This negative feedback loop in the Bim-caspase-3 axis is important for regulating the survival and activity of osteoclasts.Introduction: Bim is a member of the proapoptotic Bcl-2 family and regulates the mitochondrial apoptosis pathway. Bim expression is post-translationally regulated in osteoclasts (OCs) through ubiquitin/proteasome pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…4). The initial high levels of Bim proteins (especially BimEL) may mediate the apoptosis-inducing effect of anisomycin, while caspase-3-dependent degradation of Bim proteins may function as a negative feed-back mechanism [39]. The activation pattern of JNK is consistent with its role in the initiation of intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…4). The initial high levels of Bim proteins (especially BimEL) may mediate the apoptosis-inducing effect of anisomycin, while caspase-3-dependent degradation of Bim proteins may function as a negative feed-back mechanism [39]. The activation pattern of JNK is consistent with its role in the initiation of intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 63%
“…We did not examine the phosphorylation status of the Bim isoforms in this study, but we found, somewhat unexpectedly, a decreased level of Bim protein in both cell lines. It may represent a negative feed-back mechanism in the regulation of the intrinsic pathway of apoptosis [39].…”
Section: Mapks Are Differentially Affected By Anisomycin Treatment Inmentioning
confidence: 99%
“…Mcl-1, Bim, and Bcl-xL can be degraded by active caspases in dying cells, [34][35][36][37][38][39] which might also contribute to the observed decrease of these 3 proteins (supplemental Figure 3). …”
Section: -33mentioning
confidence: 99%
“…Bim may be degraded by caspase-3 as a negative feedback mechanism in osteoclasts (46). The caspase-cleaved form of Lyn exerts a negative feedback on imatinib-mediated chronic myelogenous leukemia cell apoptosis that is entirely dependent on its kinase activity (47).…”
Section: Tdp-43 Cleavage Leads To the Attenuation Of Tdp-43-inducedmentioning
confidence: 99%